2014
DOI: 10.1088/1367-2630/16/10/105008
|View full text |Cite
|
Sign up to set email alerts
|

Proper motions of young stellar outflows in the mid-infrared with Spitzer II HH 377/Cep E

Abstract: We have used multiple mid-infrared observations at 4.5 μm obtained with the infrared array camera, of the compact ∼ ′ ( 1.4 ) young stellar bipolar outflow Cep E to measure the proper motion of its brightest condensations. The images span a period of ∼6 yr and have been reprocessed to achieve a higher angular resolution ∼ ″ ( 0.8 ) than their normal beam ∼ ″( 2 ). We found that for a distance of 730 pc, the tangential velocities of the north and south outflow lobes are ± 62 29 and ± − 94 26 km s 1 respectively… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Research areas concerning strong magnetic fields focus on the study of experimentally observed highly excited atomic and molecular states (i.e., Rydberg states) in magnetic fields, fundamental aspects such as nuclear dynamics and nonadiabatic effects of atomic/molecular structure in strong magnetic fields and also calculations regarding the electronic structure of atoms, molecules, and condensed matter in magnetic fields . In a recent study, it has been shown that H 2 molecular gas moves at highly supersonic velocities without getting dissociated, which suggests either a very efficient mechanism to reform H 2 molecules or the shielding of H 2 gas by a strong magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Research areas concerning strong magnetic fields focus on the study of experimentally observed highly excited atomic and molecular states (i.e., Rydberg states) in magnetic fields, fundamental aspects such as nuclear dynamics and nonadiabatic effects of atomic/molecular structure in strong magnetic fields and also calculations regarding the electronic structure of atoms, molecules, and condensed matter in magnetic fields . In a recent study, it has been shown that H 2 molecular gas moves at highly supersonic velocities without getting dissociated, which suggests either a very efficient mechanism to reform H 2 molecules or the shielding of H 2 gas by a strong magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, a brief description of the principal outcomes from the papers published in this New Journal of Physics focus issue is given. Noriega-Crespo et al (2014) show that tangential velocities of the north and south bipolar Cep E outflow lobes are slightly different (62 ± 26 km s −1 and 94 ± 26 km s −1 , respectively). Both observations and models agree on the fact that the molecular hydrogen gas moves at high supersonic velocities without being dissociated.…”
mentioning
confidence: 86%
“…The proper motions of the H 2 bright shock structures, NB and HH377, were determined by Noriega-Crespo et al (2014) and correspond to tangential velocities of (70 ± 32) km s −1 and (106 ± 29) km s −1 for the northern and southern components, respectively, after correcting for the recently revised distance to Cep E-mm (820 pc instead of 730 pc). Taking into account the radial jet velocity determination from the CO observations, this results in an revised jet inclination angle of 47 • with respect to the plane of the sky, close to the determination by Lefloch et al (2015).…”
Section: The Sourcementioning
confidence: 99%